2008
DOI: 10.1029/2007tc002134
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the seismogenic layer thickness from the upper crust structure of the Umbria‐Marche Apennines (central Italy)

Abstract: [1] We reconstruct the subsurface geology in a region of the northern Apennines (central Italy) where a protracted extensional sequence occurred in 1997-1998 with maximum magnitude M = 6.0. Our study is mainly based on the interpretation of three reprocessed seismic reflection profiles crossing the epicentral area, which constrain the subsurface geometry to a depth of about 12 km where most of the shallow seismicity occurs. Comparing the subsurface setting with accurately determined earthquake locations, we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 40 publications
1
59
1
Order By: Relevance
“…In addition, the best fit of the GPS velocity data is obtained considering some degree of creeping along a portion of the GuF. The mechanical behaviour of the west-dipping GuF is still debated in the literature (Boncio et al, 2000;Mirabella et al, 2004Mirabella et al, , 2008Barchi and Ciaccio, 2009 Westaway et al, 1989) that occurred in 1984 in the area (namely, the Gubbio earthquake) occurred a few kilometres apart (see location in Fig. 1a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the best fit of the GPS velocity data is obtained considering some degree of creeping along a portion of the GuF. The mechanical behaviour of the west-dipping GuF is still debated in the literature (Boncio et al, 2000;Mirabella et al, 2004Mirabella et al, , 2008Barchi and Ciaccio, 2009 Westaway et al, 1989) that occurred in 1984 in the area (namely, the Gubbio earthquake) occurred a few kilometres apart (see location in Fig. 1a).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that the mainshocks of the 1997 Colfiorito Earthquakes, in the Northern Apennines of Italy, nucleate within such formation along normal faults at a depth of about 6 km [Barchi, 2002;Miller et al, 2004;Mirabella et al, 2007]. In particular, the spatial and time evolution of the seismic sequence has been modeled as directly controlled by fluid migration, initially trapped by the Triassic Evaporites [Miller et al, 2004].…”
Section: Inferred Slip Behaviormentioning
confidence: 99%
“…It has been recently observed that the mainshocks of one of the best documented extensional seismic sequences in the world, the 1997 Colfiorito sequence in the UmbriaMarche Apennines, were located along normal faults and TECTONICS, VOL. 27, TC4017, doi:10.1029/2007TC002230, 2008 nucleated within evaporitic rocks [i.e., the Triassic Evaporites; Barchi, 2002;Miller et al, 2004;Mirabella et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed interpretation, sketched in Figure 2, provides that such activity is mostly produced by the relative motion among the outer sector of the belt, that stressed by the Adria plate is undergoing lateral escape and uplift, and the inner less mobile zones. The escaping material only includes the sedimentary cover, decoupled from its crustal basement at seismogenic depths (of the order of 6 -10 km) by mechanically weak lithological horizons, as evidenced by seismic survey [11] [12] and borehole data [13]- [15]. In particular, a Late Triassic evaporitic layer (Burano formation [16]) forms the base of the Meso-Cenozoic sedimentary cover of most of the Romagna-Marche-Umbria and Toscana-Emilia wedges [17]- [20].…”
Section: Introductionmentioning
confidence: 99%